Analisis Eight Golden Rules pada Sistem Informasi LPPM Universitas XYZ - Rebecca La Volla Nyoto; Mariza Devega; Y Yuhelmi; N Nyoto (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
This study aims to analyze the interface quality of the Research and Community Service Information System (SIPP) at Universitas XYZ using Ben Shneiderman’s Eight Golden Rules. SIPP plays an essential role in managing research and community service activities carried out by university lecturers. However, no previous studies have specifically evaluated the system’s interface design in accordance with recognized user interface principles. This research adopts a qualitative approach through two main methods: participatory observation and expert review. The researcher actively used the system as a user to identify real-world usability issues, while the expert review involved a practitioner with UI/UX expertise. The analysis revealed that several principles of the Eight Golden Rules have not yet been fully implemented, such as limited feedback on user actions, absence of shortcuts to facilitate navigation, and a lack of confirmation prompts during critical operations. Based on these findings, interface improvement recommendations were developed in the form of wireframes using Balsamiq Cloud to enhance usability, control, and efficiency for lecturers at Universitas XYZ as system’s primary users.